Whole Genome Sequencing of Sunflower Root-Associated Bacillus cereus. (August 2021) - Babalola, Olubukola Oluranti; Adeleke, Bartholomew Saanu; Ayangbenro, Ayansina Segun
In recent times, diverse agriculturally important endophytic bacteria colonizing plant endosphere have been identified. Harnessing the potential of Bacillus species from sunflower could reveal their biotechnological and agricultural importance. Here, we present genomic insights into B. cereus T4S isolated from sunflower sourced from Lichtenburg, South Africa. Genome analysis revealed a sequence read count of 7 255 762, a genome size of 5 945 881 bp, and G + C content of 34.8%. The genome contains various protein-coding genes involved in various metabolic pathways. The detection of genes involved in the metabolism of organic substrates and chemotaxis could enhance plant-microbe interactions in the synthesis of biological products with biotechnological and agricultural importance.